A Linear-to-Circular Polarizer Using Split Ring Resonators - Chen, Juan; Zhang, Anxue (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A transmission polarizer with one layer of splitting ring resonator to realize a linearto- circular polarization rotator is presented. Based on the accurate design of anisotropic metamaterials, high conversion efficiency and 8 % frequency band are achieved. Microwave experiments were performed to realize these ideas successfully and results are in excellent agreement with numerical simulations.